(untitled) (Педагогіка вищої та середньої школи, 2007)
The article deals with the experience of a methodical work of school number 122 in improvement of teachers skills: it gives the foundation of upbringing and developed opportunities of different forms of a methodical work, structural components and a directivity of a personal orientation o f its content.